Design and implementation of a wireless capsule suitable for autofluorescence intensity detection in biological tissues. - Al-Rawhani, M; Chitnis, D; Beeley, J; Collins, S; Cumming, DR (2013)
We report on the design, fabrication, testing, and packaging of a miniaturized system capable of detecting autofluorescence (AF) from mammalian intestinal tissue. The system comprises an application-specific integrated circuit (ASIC), light-emitting diode, optical filters, control unit, and radio transmitter. The ASIC contains a high-voltage charge pump and single-photon avalanche diode detector (SPAD). The charge pump biases the SPAD above its breakdown voltage to operate in Geiger mode. The SPAD offers a photon detection efficiency of 37% at 520 nm, which corresponds to the AF emission peak of the principle human intestinal fluorophore, flavin adenine dinucleotide. The ASIC was fabricated using a commercial triple-well high-voltage CMOS process. The complete device operates at 3 V and draws an average of 7.1 mA, enabling up to 23 h of continuous operation from two 165-mAh SR44 batteries.